2021
DOI: 10.3389/fonc.2021.667496
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on Preoperative Inflammatory Indices and ICG-R15 for Prediction of Liver Failure After Hepatectomy in HCC Patients

Abstract: ObjectiveTo establish a nomogram based on inflammatory indices and ICG-R15 for predicting post-hepatectomy liver failure (PHLF) among patients with resectable hepatocellular carcinoma (HCC).MethodsA retrospective cohort of 407 patients with HCC hospitalized at Xiangya Hospital of Central South University between January 2015 and December 2020, and 81 patients with HCC hospitalized at the Second Xiangya Hospital of Central South University between January 2019 and January 2020 were included in the study. Totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The 90-day mortality rate in patients with PHLF was 9.1% when compared with 0% in patients without PHLF. Although previous studies on HBV-DNA level, ICG-R15, and PT have been reported to predict PHLF (44,45), our results demonstrated the degree of cirrhosis as assessed by our reported pre-operative CSS was an additional and significant independent predictor for PHLF. Among the factors which were found in our study to be strongly correlated with PHLF, pre-operative CSS and intra-operative DSM were the most significant predictors (all P<0.001).…”
Section: Discussioncontrasting
confidence: 79%
“…The 90-day mortality rate in patients with PHLF was 9.1% when compared with 0% in patients without PHLF. Although previous studies on HBV-DNA level, ICG-R15, and PT have been reported to predict PHLF (44,45), our results demonstrated the degree of cirrhosis as assessed by our reported pre-operative CSS was an additional and significant independent predictor for PHLF. Among the factors which were found in our study to be strongly correlated with PHLF, pre-operative CSS and intra-operative DSM were the most significant predictors (all P<0.001).…”
Section: Discussioncontrasting
confidence: 79%
“…However, it only included patients with HCC (diameter ≥ 10 cm), and its inclusion of intraoperative blood loss could not provide an accurate prediction of PHLF preoperatively. The nomogram constructed by Fang incorporates cirrhosis, but its assessment of cirrhosis is based on imaging evaluation rather than histologically confirmed ( 27 ). Therefore it is less accurate for the diagnosis of early occult cirrhosis, while its inclusion of intraoperative blood loss, like that of Xu, makes it difficult to assess PHLF preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several models were established to predict PHLF but exhibited obvious heterogeneity. Some nomograms were derived from data of patients with benign and malignant lesions ( 15 ), while some nomograms incorporated both preoperative and intraoperative variables ( 15 , 25 ), and some nomograms were based on analysis of both minor and major hepatectomies ( 17 , 18 , 26 ). Recently, Chin and colleagues ( 27 ) created a PHLF prognostic nomogram for major hepatectomy; however, the study involved patients with either HCC or colorectal liver metastasis.…”
Section: Discussionmentioning
confidence: 99%